A rural‐urban comparison of self‐management in people living with cancer following primary treatment: A mixed methods study. Issue 10 (19th August 2022) - Nelson, David; McGonagle, Ian; Jackson, Christine; Gussy, Mark; Kane, Ros
Abstract: Objective: To investigate and compare self‐management in people living with cancer following treatment, from rural and urban areas in the United Kingdom where there is a significant evidence gap. Methods: A cross‐sectional explanatory sequential mixed methods design. This involved a self‐completion questionnaire that collected data on demographics, self‐management using the PAM‐13 and rural‐urban residence and 34 in‐depth interviews that aimed to explore and compare the barriers and facilitators to self‐management in rural and urban settings. Results: 227 participants completed the questionnaire: mean age 66.86 (±11.22). Fifty‐two percent ( n = 119) were female and 48% ( n = 108) were male. Fifty‐three percent ( n = 120) resided in urban areas and 45 % ( n = 103) in rural areas. Participants had a range of different types of cancer but the three most common were breast ( n = 73), urological ( n = 53), upper and lower gastrointestinal ( n = 41). Rural respondents (63.31 ± 13.66) were significantly ( p < 0.05) more activated than those in urban areas (59.59 ± 12.75). The barriers and facilitators to self‐management identified in the interviews were prevalent in both rural and urban settings but some barriers were more explicit in rural settings. For example, there was a lack of bespoke support in rural areas and participants acknowledged how travelling long distances to urban centres for support groups was problematic. Equally, there were barriers and facilitators that were not necessarily unique to either geographic setting. Conclusion: Whilst the active treatment phase can present considerable challenges for people living with cancer in rural areas the findings suggest that the rural environment has the potential to increase engagement with self‐management in the transition to survivorship. The rigorous mixed methods design has led to different and complementary conclusions that would not have been possible had either quantitative or qualitative methods been used in isolation.